Alterations Induced by Bangerter Filters on the Visual Field: A Frequency Doubling Technology and Standard Automated Perimetry Study - Costantino Schiavi; Filippo Tassi; Alessandro Finzi; Mauro Cellini (Journal of Ophthalmology)
Purpose. To investigate the effects of Bangerter filters on the visual field in healthy and in amblyopic patients. Materials and Methods. Fifteen normal adults and fifteen anisometropic amblyopia patients were analysed with standard automated perimetry (SAP) and frequency doubling technology (FDT) at baseline and with filters 0.8 and 0.1. Results. With 0.1 filter in SAP there was an increase of MD compared with controls (−10.24 ± 1.09 dB) in either the amblyopic (−11.34 ± 2.06 dB; P<0.050) or sound eyes (−11.34 ± 1.66 dB; P<0.030). With filters 0.8 the PSD was increased in the amblyopic eyes (2.09 ± 0.70 dB; P<0.007) and in the sound eyes (1.92 ± 0.29 dB; P<0.004) compared with controls. The FDT-PSD values in the control group were increased with the interposition of the filters compared to baseline (0.8; P<0.0004 and 0.1; P<0.0010). We did not find significant differences of the baseline PSD between amblyopic eyes (3.80 ± 2.21 dB) and the sound eyes (4.33 ± 1.31 dB) and when comparing the filters 0.8 (4.55 ± 1.50 versus 4.53 ± 1.76 dB) and 0.1 (4.66 ± 1.80 versus 5.10 ± 2.04 dB). Conclusions. The use of Bangerter filters leads to a reduction of the functionality of the magno- and parvocellular pathway.